PERAN DAN KERJA SAMA ANTAR LEMBAGA DALAM MENANGANI KASUS PENCURIAN MINYAK DI LAUT - Anam, Khoirul; Harahap, M.Syahnan (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2024)
Oil theft at sea is a complex transnational crime that causes significant losses to the state. This research aims to analyse the role and cooperation between institutions in handling cases of oil theft at sea using the juridical normative method. The main focus is to examine the relevant laws and regulations and their implementation in handling cases. The results show that the handling of oil theft at sea involves various institutions such as the Navy, Police, Bakamla, Directorate General of Sea Transportation, and Directorate General of Customs. Law No. 32/2014 on Maritime Affairs is the main legal basis that regulates the authority of each institution. However, there are overlapping authorities that hamper the effectiveness of case handling. Inter-agency cooperation is realised through joint operations, information exchange and investigation coordination. However, there are still obstacles such as sectoral ego, differences in operating procedures, and limited infrastructure. Efforts to increase cooperation were made through the establishment of a joint task force and the signing of a memorandum of understanding between agencies. This study concludes that optimising the role and cooperation between agencies requires improved regulations to clarify the division of authority, improved coordination, and strengthened institutional capacity. Recommendations include revising the Marine Law, establishing an integrated command centre, and increasing the budget and technology for marine surveillance.